Antibacterial Activities of Parijoto (Medinilla speciosa Blume) Fruit Extracts Against Clinical Isolates of Salmonella typhi and Shigella dysenteriae - Tiana Milanda; Melisa I. Barliana; Rosidah Rosidah; Arif S.W Kusuma (Pharmacology and Clinical Pharmacy Research, 2021)
Medinilla speciosa (M. speciosa) Blume is a plant originating from Mount Muria, Kudus District, Central Java, Indonesia. Its fruit has been used by the local community to treat mouth sores, diarrhea, inflammatory, hyperlipidemia, cancer, bacterial infection and nutrients for pregnant women. However, the antibacterial activity against Salmonella typhi (S. typhi) and Shigella dysentriae (S. dysentriae) is yet unknown. Thus, the aim of this study was to determine the antibacterial activities of M. speciosa fruit extracts against clinical strain of S. typhi and S. dysentriae. Plant determination and sample preparation were conducted. The fruits of M. speciosa were extracted by gradual maseration using n-hexane, ethyl acetate and methanol as solvents. Phytochemicals were screened by Fransworth method. Antibacterial activity was determined using agar well diffusion. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values and comparison study of antibacterial activity were determined. The results showed that all of the extracts exhibited antibacterial activities, with the greatest activity  shown by the methanol extract. This extract was more effective against S. dysenteriae  than S. typhi, as evidenced by the largest inhibition diameter and lowest MIC (25 mg/mL) and MBC (50 mg/mL) values. With regard to the results of phytochemical screening, the antibacterial activity of methanol extract could be due to the presence of alkaloids, flavonoids, polyphenols, quinones, saponins and tannins. From the comparative antibacterial activity value indicated that in order to give the same inhibition diameter with 1 ppm of chloramphenicol, 312.3 ppm methanol extract is needed. It can be conclude that M. speciosa fruit has a potential to be developed as natural antibacterial agent, especially to treat bacillary dysentery